2002
DOI: 10.1207/153276502760242350
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Evaluation of the Perceptions of Health of Elders of Different Multicultural Backgrounds

Abstract: The purpose of this study was to discover the perceptions of health and the health maintenance practices of 4 different cultural and ethnic groups. Interviews were conducted at senior citizen centers in and around a large metropolitan center in Texas. Five Native Americans, 44 African Americans, 32 Latinos, and 13 Vietnamese were questioned about their views on being healthy. Huff and Kline's Cultural Assessment Framework was used to analyze the responses. Functionality and independence were dominant themes no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 5 publications
(6 reference statements)
1
13
0
Order By: Relevance
“…They also parallel the work of other scholars in the health conception field who hold the view that culture gives meaning to personal experiences of health and illness (Angel & Thoits, 1987;Hufford, 1992;Kleinman, 1978;Jobanputra & Furnham, 2005;Jovchelovitch & Gervais, 1999;O'Connor, 1998;Torsch & Ma, 2000). The findings of the present study also support the notion that cultural differences exist in the meaning people ascribe to health (Felton et al, 1997;Hakim & Wegmann, 2002;Hjelm et al, 2005;Jobanputra & Furnham, 2005;Torsch & Ma, 2000).…”
Section: Principal Research Findingssupporting
confidence: 85%
See 3 more Smart Citations
“…They also parallel the work of other scholars in the health conception field who hold the view that culture gives meaning to personal experiences of health and illness (Angel & Thoits, 1987;Hufford, 1992;Kleinman, 1978;Jobanputra & Furnham, 2005;Jovchelovitch & Gervais, 1999;O'Connor, 1998;Torsch & Ma, 2000). The findings of the present study also support the notion that cultural differences exist in the meaning people ascribe to health (Felton et al, 1997;Hakim & Wegmann, 2002;Hjelm et al, 2005;Jobanputra & Furnham, 2005;Torsch & Ma, 2000).…”
Section: Principal Research Findingssupporting
confidence: 85%
“…Interviews followed a structured format, using a predefined set of questions (Appendix A). The questions were adapted from interview questions that have been used in previous studies (Ailinger & Causey, 1995;Ailinger et al, 2007;Hakim & Wegmann, 2002;McMullin, 2005) and were translated in…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several ethnic minorities demonstrate a strong faith in God to heal, believing that God is in control of 6 E. Cole et al their health, instead of the formal medical community (Swinney, 2002). For some African Americans, maintaining health comes from living "good," which includes religious faith, prayer, and church attendance (Hakim & Wegmann, 2002). McAuley, Pecchioni, and Grant (2000) found that, in comparison to European Americans, African Americans more commonly describe particular role expectations for God in health and illness, especially in the healing process.…”
Section: Definitions and Research Questionsmentioning
confidence: 99%